Writing across difference: theory and intervention - Daniel, James Rushing, editor; Malcolm, Katie, editor; Rai, Candice, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2022)
Increasingly divided by economic inequality, racial injustice, xenophobic violence, and authoritarian governance, writing studies scholars have developed responsive theories and practices to engage students, teachers, administrators, and citizens. The first collection to focalize difference as such, gathering scholars offering theoretical, methodological, and pedagogical resources for understanding, interrogating, negotiating, and writing across difference.--Provided by publisher.
Introduction: centering difference in composition studies / James Rushing Daniel, Katie Malcolm, Candice Rai -- An embodied history of translingualism / Juan C. Guerra -- 'Gathering Dust in the Dark': inequality and the limits of composition / James Rushing Daniel -- Desconocimiento: a process of epistemological unknowing through rhetorical nepantla / Iris D. Ruiz -- Exploring discomfort using markers of difference: constructing anti-racist and anti-ableist teaching practices / Stephanie L. Kerschbaum -- Whole self rhetoric: teaching the justice situation in the composition classroom / Nadya Pittendrigh -- Re-writing the biology of difference: how a writing-centered, case-based curricular approach can reform undergraduate science / Megan Callow and Katherine Xue -- Disability identity and institutional rhetorics of difference / Neil F. Simpkins -- Interrogating the 'Deep Story': storytelling and narratives in the rhetoric classroom / Shui-yin Sharon Yam -- Designing across difference: intersectional, interdependent approaches to sustaining communities / Laura Gonzales and Ann Shivers-McNair -- Antiracist translingual praxis in writing ecologies / Sumyat Thu, Katie Malcolm, Candice Rai, and Anis Bawarshi -- Confronting super-diversity again: a multidimensional approach to teaching and researching writing at a global university / Jonathan Benda, Cherice Escobar Jones, Mya Poe, and Alison Y.L. Stephens.
Keywords: English language -- Rhetoric -- Study and teaching (Higher) -- Social aspects -- United States; English language -- Composition and exercises -- Study and teaching (Higher) -- Social aspects -- United States; Individual differences; Interdisciplinary approach in education -- United States; Discrimination in higher education -- United States